Wykwintne zupy : delikatne, klarowne, kremowe - Imhoff, Heinz; Imhoff, Heinz (Warszawa : Warszawski Dom Wydawniczy, 1992)
A selection of various types of soups.
Includes index.
Translation of: Feine suppen.
Keywords: Cooking; Soups